A novel mechanism for guanidino succinic acid (GSA) and technetium-99m-GSA, a novel agent for muscarinic acetylcholine receptor imaging - Kara, G (Springer, 2004)
[Abstract Not Available]
17th Annual Congress of the European-Association-of-Nuclear-Medicine -- SEP 04-08, 2004 -- Helsinki, FINLAND